KNOWLEDGE ABOUT MOBILE LEARNING AND INTEGRATION OF MOBILE DEVICES BY FACULTY OF UNIVERSIDAD NACIONAL DE COSTA RICA - Chacón-Ortiz, Manuel (2017)
There is a debate about the concept of mobile learning and the emergence of mobile devices in higher edcation. This research was developed from a qualitative approach, with the participation of eight university faculty members through a discussion group. The objective was to understand the following aspects: (a) the faculty’s concept of mobile learning; (b) their perspective on using smartphones and tablets in the classroom; and, (c) the implications in the teacher-student relationship upon the incorporation of these devices in higher education. From the data obtained, we can confirm that there is a construction of the concept of mobile learning that comes from everyday praxis. The incursion of tablets and smartphones in the classrooms has been natural. Concerns regarding the management and control of these devices in class were identified, in addition to the concern about their educational benefits or harms. It is concluded that there is an interest and agreement about mobile learning and the use of mobile technology in higher education.